"Does that mean I can't use my phone to pay when I'm in the Maccas drive thru?": Younger drivers' uncertainty and attitude toward smartphone law and punishment. (September 2021) - Kaviani, F.; Benier, K.; Robards, B.; Young, K.L.; Koppel, S.
Highlights: Mixed methods approach explored younger drivers' perceptions on smartphone law. Belief smartphone law is ambiguous and unreasonable frames justifications for use. Surreptitious use of navigation and music apps common among Probationary drivers. Smartphone behaviours learned during probationary period continue into full licence. Severity of punishment perceived as incommensurate with crash risk. Abstract: This study employed a mixed methods approach (a survey [ n  = 2, 774] and focus groups [ n  = 16]) to understand the perceptions of younger drivers (18–25) on current smartphone laws in the Australian state of Victoria. First, by analysing quantitative data gathered from an online survey regarding smartphone laws, perceptions of punishment when breaking the law, and attitudes to both the law and fines, this study found younger drivers were less likely to understand the law around phone use while driving, even after direct or indirect experience with police. Additionally, the severity and impact of fines were perceived as more impactful and severe among younger drivers, women, and those on lower incomes, and the most common types of illegal use younger drivers engaged with were navigation, music applications, and hands-free calling, mostly facilitated through Bluetooth with their device placed out of sight. Consequently, focus groups were conducted with a subset of these younger drivers to explore these findings in more depth. It was revealed that smartphone laws were perceived to be ambiguous, at times unreasonable, and difficult to access conclusive information regarding the law or receive information throughout the Graduated Licencing Program. Additionally, of full licenced drivers breaking smartphone laws ( n  = 807), 61.7 percent never used a cradle. Among probationary drivers breaking the law ( n  = 209), 76.1 percent never used a cradle. This suggests rampant surreptitious illegal use. As such, younger drivers learning to drive are also learning methods to avoid punishment while breaking smartphone laws. This included not using a cradle and opting instead for Bluetooth connectivity or engaging in hand-held use, a choice that continued into Full Licensed driving. The severity of punishment was not common knowledge and was perceived to be incommensurate to the risks associated with certain types of use. In their opinion all of these factors reduced the legitimacy of the law. Addressing these factors with evidence-based countermeasures may increase compliance and road safety.